Authoritarian resilience in Morocco after the Arab spring: a critical assessment of educational exchanges in soft power. Issue 3 (27th May 2018) - Hill, J. N. C.
ABSTRACT: The aim of this article is to critically assess Joseph Nye's claims about student exchange programmes by examining the impact of Morocco's educational relationship with the EU on the kingdom's political development during and since the Arab Spring. Nye maintains that such schemes are important sources of soft power which Western countries can use to promote their values – including that of democracy – in the societies of the visiting students. Despite tens of thousands of its citizens enrolling in European universities each year, however, Morocco is scarcely any more democratic today than it was when the Arab Spring began. The article considers what the country's non-democratisation means for the EU's soft power and this facet of Nye's thesis.